Physical characteristics of selected and non-selected high school rugby union players - Fowkes, R. A. (Journal of Australian Strength and Conditioning, 2020)
Physical characteristics were compared between players selected and not selected to play First XV in an Australian independent school rugby union program. Fifty-two male subjects from the same rugby program (age: 17.1 ± 0.6 years, height 181.1 ± 6.0 cm, body mass 83.7 ± 10.5 kg) underwent a physical testing battery to quantify height, body mass, strength (bench press, weighted chin, back squat, deadlift), speed (5, 10, 20m), momentum (average velocity * body mass), cycling peak power output (6s maximal sprint) and running capacity (1.2km time trial). Data was assessed as selected (S) versus non-selected (NS) within the positional groupings of forwards and backs. S players in both positional groups were heavier (Forwards 94.5 vs 86.2kg, Backs 80.2 vs 73.6kg), had greater lower body strength (Forwards back squat 140.0 vs 112.8kg, deadlift 160.4 vs 125.7kg; Backs back squat 124.4 vs 107.3kg, deadlift 134.4 vs 120.3) and higher momentum at 0-5m (Forwards 438 vs 390 kg/s,Backs 384 vs 350kg/s), 0-10m (Forwards 513 vs 459kg/s,Backs 452 vs 410kg/s) and 0-20m (Forwards 595 vs 531kg/s,Backs 528 vs 476 kg/s). S forwards had greater upper body strength (Bench press 114.4 vs 86.8kg, weighted chin 27.5 vs 16.2kg), relative strength (bench press 1.22 vs 1.01kg/kg, weighted chin 1.30 vs 1.19kg/kg, back squat 1.48 vs 1.32kg/kg, deadlift 1.70 vs 1.47 kg/kg) and cycling peak power output (1286 vs 1116W) than NS forwards. To reach the required physical level, players should aim to increase strength, power, and body mass, while maintaining sprint speed and running capacity. Physical characteristics of S players within an independent school rugby program compared favourably to normative data from academy players of similar age.